Upper Cretaceous ammonites from the Coon Creek Tongue of the Ripley Formation at its type locality in McNairy County, Tennessee - Cobban, W; Kennedy, W (1994)
The ammonite fauna of the Coon Creek Tongue of the Ripley Formation at its type locality in McNairy County, Tennessee, is described. This fauna has generally been placed in the lower Maastrichtian, but it is here attributed to the upper Campanian, inasmuch as two of the characteristic species present, N.(N.) hyatti and J. nodosus, are confined to the upper Campanian in western Europe. A younger ammonite fauna of early Maastrichtian age is present, however, in the Coon Creek Tongue of Mississippi, Alabama, and Georgia. -from Authors